Characterization of Aluminum Black Dross Leachate from the Tertiary Smelting Industry in Jombang, East Java - Lukita, Maya; Riani, Etty; Ismail, Ahyar; Abidin, Zaenal (UI Scholars Hub, 2025)
Aluminum black dross is a type of hazardous waste because it readily reacts with water to produce gas. Previous studies have reported the potential dangers of aluminum black dross to humans and the environment. This study examined the characteristics of aluminum black dross from Jombang Regency, East Java Province. The properties investigated included the volume of gas produced during leaching, the solubility of salts and aluminum under various conditions, and the mineral characteristics analyzed via Fourier transform infrared (FTIR) spectroscopy, X-ray fluorescence (XRF), and X-ray diffraction (XRD). Notably, 115 mL of gas was produced from each 0.5 g of aluminum black dross that reacted with water, and the gas was identified as a mixture of hydrogen, methane, and ammonia. Alkaline conditions (pH = 10) during the leaching process were optimal for both gas production and aluminum solubility. The highest amount of dissolved salts was observed under acidic leaching conditions. The nitride phase, responsible for producing corrosive ammonia, was detected via FTIR and XRD analyses. Aluminum black dross is significant as an alumina-based material owing to its high Al2O3 content, which increases after leaching, as demonstrated via XRF measurements. This study provides an alternative leaching process for aluminum black dross based on the gases produced and the residue generated. This study presents the characterization of aluminum black dross as hazardous waste due to its emission of gases harmful to human health and the environment. The results highlight the urgent need for implementing safe handling and management practices for aluminum black dross to minimize potential risks